2022
DOI: 10.1111/jeb.14026
|View full text |Cite
|
Sign up to set email alerts
|

The costs and benefits of larger brains in fishes

Abstract: and we thus require evolutionary explanations for why some organisms invest more heavily into their brains than others. A wide range of hypotheses have been proposed in this regard, and these fall into two broad categories: first, there are hypotheses concerning the costs of and constraints on brain size increases, with a focus on identifying those conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 109 publications
1
2
0
Order By: Relevance
“…Additionally, although we found that reaching the food inside the long cylinder was more challenging, this level of difficulty might still have been too simple to reveal the fine-graded cognitive differences between individuals living in large and small groups. Nevertheless, our results are in line with other studies finding little support for the sociality and cognition hypothesis in fishes [43,44,80].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, although we found that reaching the food inside the long cylinder was more challenging, this level of difficulty might still have been too simple to reveal the fine-graded cognitive differences between individuals living in large and small groups. Nevertheless, our results are in line with other studies finding little support for the sociality and cognition hypothesis in fishes [43,44,80].…”
Section: Discussionsupporting
confidence: 92%
“…The mosaic brain hypothesis proposes that structural variation in the brain and its constituent functionally specialized compartments—regulated by genetic architectures (Hager et al., 2012; Hibar et al., 2015; Noreikiene et al., 2015; Zwarts et al., 2015) and developmental patterning (Sylvester et al., 2010)—may evolve independently of body size. Adaptive brain mosaicism has been identified in eusocial insects in association with reproductive and ergonomic division of labor (Godfrey & Gronenberg, 2019; Gordon & Traniello, 2018; Kamhi et al., 2016; Muscedere & Traniello, 2012; Muscedere et al., 2014; O'Donnell et al., 2013, 2018, 2019), as well as in mice (Hager et al., 2012), fish (Fischer & Jungwirth, 2022; Tamayo et al., 2020; York et al., 2019), and primates (Harrison & Montgomery, 2017). However, brain evolution may be concerted, that is, constrained by developmental processes coupling brain size to body size and/or coordinating the development of different brain centers (Finlay & Darlington, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The above studies were predominantly conducted on endothermic species. The tradeoffs between brain size and growth rate (and thus age at maturity) and reproductive output reported for endotherms are also apparent in ectotherms (anurans: [ 13 , 14 ]; fishes: [ 15 ]; reptiles: [ 16 ]). Likewise, as in mammals [ 5 ] and birds [ 12 , 13 ], larger-brained species tend to produce larger offsprings in lineages without post-hatching provisioning (frogs: [ 17 ]; lizards [Song et al, unpublished]; chondrichthyan fishes: [ 18 ]).…”
Section: Introductionmentioning
confidence: 99%